Hematology of mountain lions (Puma concolor) in the Sierra Nevada, California, USA: effect of sex, season, or location? - Vernon C. Bleich; Becky M. Pierce; Holly B. Ernest; Jeffrey T. Villepique (California Fish and Wildlife Journal, 2020)
There is a paucity of published hematological data for wild, free-ranging mountain lions (Puma concolor). We collected such information from mountain lions occurring at mid-elevations to increase available baseline information. We captured and sampled 43 individuals in a remote part of the eastern Sierra Nevada, Inyo and Mono counties, California, USA, and present descriptive statistics and reference intervals for hematological variables of mountain lions occupying that rural area. We tested for differences between males and females, and between winter (when mule deer [Odocoileus hemionus] were abundant in diets) and summer (when smaller prey were most common in diets). Male mountain lions exhibited a greater percentage of bands (i.e., immature neutrophils) than did females. Although the mean percentage of segmented neutrophils during winter was lower than during summer, that difference disappeared when a potential outlier was removed. Mean hematocrit among mountain lions sampled at 1,200–1,800 m elevation in the Sierra Nevada was higher than that of animals sampled at sea level in Florida, but lower than that of animals sampled exclusively at elevations >2,100 m in Colorado. Mean concentrations of red blood cells and hemoglobin also were higher for Sierra Nevada mountain lions than for animals sampled in Florida. These results are consistent with expectations for animals residing at different elevations and emphasize the value of establishing baseline information for populations existing under disparate ecological conditions.